Pengembangan Media Pembelajaran Berbasis e-Learning pada Mata Pelajaran Ekonomi di SMA - Yunus, Muchtar; Rakib, Muhammad (Indonesian Journal of Educational Studies, 2016)
This research aims to develop media learning based on e-learning using Edmodo in material consumption, savings, and investment. This research was conducted in the form of development through several steps that willproduce in the form of media-based learning e-learning interesting and effective.Results of research conducted development shows that the media e-learning usingedomodo on economic subjects has appeal, in the sense of getting a response that isof interest to students and is effectively used in the learning process of economic subjects because it can improve student learning outcomes.